Can Two Human Intelligences (HIs or Noes) and Two Artificial Intelligences (AIs) Get Involved in Interlinguistic Communication? – A Transdisciplinary Quest - Ekaterini Nikolarea (Journal of Systemics, Cybernetics and Informatics)

(untitled)
The author of this paper will first define what interlinguistic communication involves. Second, she will categorize: (a) the interface between two AIs in the language they have been programmed; and (b) the interface between HIs and AIs in two distinct cases in relation to communication, by providing specific examples. Third, she will try to explain why AI is unable to get involved in interlinguistic communication, whereas healthy HIs are able to attain this task. The writer of this study will base her analysis on neuroscience (Broca and Wernicke), linguistics, translation studies and socio-cultural studies. Finally, the objective of this study is twofold: (1) to wish for a collection of articles written about how language functions in bilingual and multilingual environments as well as in international conferences and (2) to motivate scientists from different fields to learn/know how nous (human brain and mind) operates in interlinguistic situations in general and scientific interlinguistic situations in particular (e.g. IIIs Conferences). Such a kind of knowledge can lead to a better understanding of humanity.